Fundamentos filosóficos para uma crítica e legítima aplicação do direito: o operar do círculo hermenêutico na compreensão jurídica - Sá, Waltenberg Lima de (2014)
This work presents a new paradigm for legal hermeneutics, divorced from positivism and hence the legal doctrine. To do so, outlines the doctrinal framework that preceded the construction of the theoretical framework used here , the philosophical hermeneutics of Gadamer, whose keynote is in opposition to the method as the only means to get to the truth. When entering your analysis itself, seeks to work with the most important concepts, such as tradition, authority, pre-understanding and the fusion of horizons, in order to pave the way to understand what he describes as a circle hermeneutic, a key concept for the demarcation of the proposal developed here. On this, also seeks to make an evolutionary analysis of the proposals of the thinkers that preceded the gadameriano concept. Outlined the substance of philosophical hermeneutics, we proceed to the analysis of its operation in legal interpretation, printing a critical reflection on the understanding in the application of law and, as a corollary, contributing to overcome the positivist paradigm and its aporias and as for the discussion about the legitimacy of judicial decisions. Thus seeks to clarify the contribution of Gadamer to legal thought, from his philosophical hermeneutics to explain, justify and legitimize the path taken by the judge pronouncing judgments.